2022
DOI: 10.1039/d2va00023g
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship study of the impacts of hydraulic fracturing on the environment and socioeconomic activities: a novel approach to finding sustainable solutions

Abstract: Global energy governance is highly influenced by the increasing energy demand, dwindling conventional energy systems, and socioeconomic activities. However, the global COVID-19 pandemic, which started in 2020, did not only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Rainfall and temperature data are important elements in understanding water balance on a global scale, as well as studying and understanding the complexity of human-water systems (social hydrology). 6 However, rainfall patterns may vary from region to region, and in some cases, they may differ from one weather station to another in the same region. On the other hand, as supported by many studies, homogeneity in terms of theoretical distribution can be found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainfall and temperature data are important elements in understanding water balance on a global scale, as well as studying and understanding the complexity of human-water systems (social hydrology). 6 However, rainfall patterns may vary from region to region, and in some cases, they may differ from one weather station to another in the same region. On the other hand, as supported by many studies, homogeneity in terms of theoretical distribution can be found.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 6. Annual total number of rainfall events greater than 1 mm for the observed data recorded at the selected weather stations in the four nations for the 55-year period…”
mentioning
confidence: 99%